The effect of selected in ovo green light photostimulation periods on post-hatch broiler growth and somatotropic axis activity - Dishon, L. (Poult Sci, 2021)
Targeted in ovo green light (GL) photostimulation during the last days of broiler egg incubation increases embryonic expression of the somatotropic axis, similar to in ovo green light photostimulation from embryonic day (ED) 0 to the end of incubation. The aim of this study was to examine the effect of selected in ovo GL photostimulation periods on post-hatch broiler growth. Four hundred twenty fertile broiler eggs were divided into 7 treatment groups: the first incubated in the dark (standard conditions) as a negative control; the second incubated under monochromatic GL from ED0-ED20 (positive control); the third group incubated under monochromatic GL light from ED15-ED20; the fourth, fifth and sixth groups were incubated under monochromatic GL on ED16, ED17, and ED18, respectively; and the seventh group was incubated under monochromatic GL from ED18-ED20. All illumination was provided intermittently using LED lamps. After hatch, all chicks were transferred to a controlled room under standard rearing conditions. The group incubated under green light from ED18 until hatch showed similar results to the positive control group in body weights, as well as breast muscle weights (as % of body weights), and an elevation in the somatotropic axis activity during the experiment. We suggest that broiler embryos can be exposed to in ovo GL photostimulation from ED18 until hatch (hatching period), and still exhibit the same performance as obtained by photostimulation from d 0 of incubation.